2022
DOI: 10.3390/ijms23073772
|View full text |Cite
|
Sign up to set email alerts
|

Store-Operated Ca2+ Entry in Skeletal Muscle Contributes to the Increase in Body Temperature during Exertional Stress

Abstract: Exertional heat stroke (HS) is a hyperthermic crisis triggered by an excessive accumulation of Ca2+ in skeletal muscle fibers. We demonstrated that exercise leads to the formation of calcium entry units (CEUs), which are intracellular junctions that reduce muscle fatigue by promoting the recovery of extracellular Ca2+ via store-operated Ca2+ entry (SOCE). Here, we tested the hypothesis that exercise-induced assembly of CEUs may increase the risk of HS when physical activity is performed in adverse environmenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 66 publications
(123 reference statements)
0
5
0
Order By: Relevance
“… 43-45 , 113 In analogy, fast versus slow troponin isoforms were identified in the actin-containing thin filaments. 113 , 11 4 This shows that the presented analysis pipeline is suitable for studying myofiber type shifting during aging. 30 Crucial extra-sarcomeric cytoskeletal proteins were identified in skeletal muscles, including the central cytolinker plectin, 115 and members of costameres such as alpha7/beta1-integrin, 116 and alpha/beta-dystroglycan in conjunction with its membrane cytoskeletal anchor named dystrophin.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“… 43-45 , 113 In analogy, fast versus slow troponin isoforms were identified in the actin-containing thin filaments. 113 , 11 4 This shows that the presented analysis pipeline is suitable for studying myofiber type shifting during aging. 30 Crucial extra-sarcomeric cytoskeletal proteins were identified in skeletal muscles, including the central cytolinker plectin, 115 and members of costameres such as alpha7/beta1-integrin, 116 and alpha/beta-dystroglycan in conjunction with its membrane cytoskeletal anchor named dystrophin.…”
Section: Discussionmentioning
confidence: 89%
“… 117 , 118 This would enable the in-depth analysis of alterations in the levels of lateral force transmission through costameric structures in aged skeletal muscles. Since the extracellular matrix is a crucial structural component of muscles, 11 9 and majorly involved in reactive myofibrosis in neuromuscular diseases, 120 , 121 it is encouraging that representative markers of the basal lamina, endomysium, perimysium, epimysium and tendon could be detected by proteomics in crude muscle tissue extracts. In conclusion, the mass spectrometric screening of senescent mouse muscles has been successfully applied to establish a proteomic reference map for future sarcopenia research.…”
Section: Discussionmentioning
confidence: 99%
“…Note the bump-phase (indicatedby arrows in Figure 6 A and Figure 7 A), which was previously characterized in two papers by Michelucci and colleagues as the phase of activation of SOCE [ 81 , 82 ]. To demonstrate whether the increased fatigue resistance registered in EDL muscles exercised ex vivo at 36 °C (pH 7.4) and at 7.2 (25 °C) was due to increased Ca 2+ entry via SOCE, we performed parallel experiments conducted using either: (i) a Ca 2+ -free solution, in which Ca 2+ was replaced by an equimolar concentration of Mg 2+ ; or (ii) a Ca 2+ -containing solution supplemented with 10 μM BTP-2 ( Figure 6 C and Figure 7 C), an established inhibitor of SOCE [ 77 , 79 , 90 , 91 , 92 ]. These experiments indicated that the enhanced fatigue resistance of EDL muscles exercised ex vivo at 36 °C (pH 7.4) and at pH 7.2 (25 °C) containing ex vivo assembled CEUs ( Figure 4 and Figure 5 ) was effectively due to the entry of extracellular Ca 2+ via SOCE, as inhibition of Ca 2+ entry results in faster decay of contractile force ( Figure 6 C and Figure 7 C).…”
Section: Resultsmentioning
confidence: 99%
“…Muscle activity generates heat: the temperature of human skeletal muscle can increase from 33 °C up to 39 °C during exercise [ 94 ], raising the possibility that heat-induced Ca 2+ influx via SOCE could play a role in skeletal muscle physiology. We have recently shown that exercise-dependent assembly of CEUs could contribute to exertional heat stroke when exercise is performed in adverse environmental conditions [ 92 ]. In the present study, the assembly of functional CEUs was favored by physiological temperature, when compared to 25 °C.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, Ca 2+ entry plays a role in contracture of biopsies and MH susceptibility. We have also recently showed that assembly of CEUs during exercise contributes to the increase in body temperature during exertional stress ( Girolami et al, 2022 ). One puzzling question to answer in our future work would be: the constitutively active SOCE in Casq1-null fibers may contribute to the MH/HS susceptibility of these mice?…”
Section: Discussionmentioning
confidence: 99%